Optimisation of peptides that actively cross the tympanic membrane by random amino acid extension: a phage display study. (7th February 2018) - Kurabi, Arwa; Schaerer, Daniel; Chang, Lisa; Pak, Kwang; Ryan, Allen F.
Abstract: Local treatment of middle ear (ME) disease currently requires surgical penetration of the tympanic membrane (TM). We previously discovered 12-mer peptides that are actively transported across the intact TM, a process that could be used for non-invasive drug delivery into the ME. To optimise transport and provide further understanding of the peptides transport mechanism, we extended two of the candidate peptides by six additional amino acids at random, and screened the resulting 18-mers libraries on TMs of rats with active bacterial otitis media (OM) for transport efficiency using phage display. Six identified peptides were individually tested in vivo for trans-TM transport to verify the tissue specificity. Three exhibited enhanced transport compared to their parent 12-mer scaffold, with the best showing an approximately nine-fold increase. Sequence analysis revealed anchor residues and structural features associated with enhanced transport. This included the prominent display of conserved sequence motifs at the extended free ends of the predicted peptide structures.